2015
DOI: 10.7863/ultra.34.5.869
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Kidney Fibrosis Using Ultrasonic Shear Wave Elastography

Abstract: Objectives The purpose of this study was to evaluate the feasibility of ultrasonic shear wave elastography for quantification of renal fibrosis in an experimental rabbit model. Methods Thirty‐eight kidneys of 19 rabbits were studied and categorized into 3 groups: group I, ureter obstruction (n = 9); group II, renal vein occlusion (n = 10); and group III, normal control (n = 19). Before surgery, we measured stiffness at the renal cortex using shear wave elastography and evaluated the sonographic findings, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
(85 reference statements)
3
20
0
Order By: Relevance
“…The values of the density ( ρ ), interfacial tension ( σ ), rigidity ( G ) and viscosity ( µ ) for blood were 1050 kg m −3 , 0.056 N m −1 , 0.0 kPa and either 3 or 5 mPa·s, respectively, while those for kidney tissue were 1100 kg m −3 , 0.056 N m −1 , either 0 kPa, 1 kPa, 2 kPa or 0.18 MPa and 3 – 23 mPa·s, respectively. These values encompass bulk-tissue values for rigidity reported for kidney from ultrasound elastography methods for frequencies below 1 kHz (Arda et al 2011; Amador et al 2011;Derieppe et al 2012; Gennisson et al 2012; Grenier et al 2013; Moon et al 2015) and a direct shear-wave method for frequencies above 6 MHz (Yang and Church 2006). It is worth noting here that in all cases for which sufficient data are available for comparison over several orders of magnitude for frequency, the values for the modulus of rigidity in tissue tend to remain the same, while values for viscosity decrease by a factor of 100 (see also Madsen et al 1983; Deffieux et al 2009; Chen et al 2013).…”
Section: Background and Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The values of the density ( ρ ), interfacial tension ( σ ), rigidity ( G ) and viscosity ( µ ) for blood were 1050 kg m −3 , 0.056 N m −1 , 0.0 kPa and either 3 or 5 mPa·s, respectively, while those for kidney tissue were 1100 kg m −3 , 0.056 N m −1 , either 0 kPa, 1 kPa, 2 kPa or 0.18 MPa and 3 – 23 mPa·s, respectively. These values encompass bulk-tissue values for rigidity reported for kidney from ultrasound elastography methods for frequencies below 1 kHz (Arda et al 2011; Amador et al 2011;Derieppe et al 2012; Gennisson et al 2012; Grenier et al 2013; Moon et al 2015) and a direct shear-wave method for frequencies above 6 MHz (Yang and Church 2006). It is worth noting here that in all cases for which sufficient data are available for comparison over several orders of magnitude for frequency, the values for the modulus of rigidity in tissue tend to remain the same, while values for viscosity decrease by a factor of 100 (see also Madsen et al 1983; Deffieux et al 2009; Chen et al 2013).…”
Section: Background and Methodsmentioning
confidence: 83%
“…Also shown are the results of Miller et al (2008b) for experimental thresholds of GCH for the LAB exposure system (squares) and the DUS system (diamonds, open symbols show the “no-effect” level at the highest outputs available); the straight lines are the best fits through the positive results for the two systems. The dashed line labeled MI =1.9 represents the upper limit on the MI for diagnostic scanners approved under the FDA’s track 3 process.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the earliest studies of renal SWE imaging were performed in animals and transplanted kidneys. Animal studies on rats and rabbits showed a direct correlation between renal cortical stiffness and renal fibrotic changes, and between an increase in cortical stiffness and a decline in renal function 19,20. In studies of transplanted kidneys, increased renal stiffness was detected in cases of transplant rejection and in patients who developed acute deterioration in renal function 2137…”
Section: Discussionmentioning
confidence: 99%
“…The values of the density (ρ), interfacial tension (σ), rigidity (G) and viscosity (µ) for blood were 1050 kg m −3 , 0.056 N m −1 , 0.0 kPa and either 3 or 5 mPa·s, respectively, while those for kidney tissue were 1100 kg m −3 , 0.056 N m −1 , either 0 kPa, 1 kPa, 2 kPa or 0.18 MPa and 3 -23 mPa·s, respectively. These values encompass bulk-tissue values for rigidity reported for kidney from ultrasound elastography methods for frequencies below 1 kHz (Arda et al 2011;Amador et al 2011;Derieppe et al 2012;Gennisson et al 2012;Grenier et al 2013;Moon et al 2015) and a direct shear-wave method for frequencies above 6 MHz . It is worth noting here that in all cases for which sufficient data are available for comparison over several orders of magnitude for frequency, the values for the modulus of rigidity in tissue tend to remain the same, while values for viscosity decrease by a factor of 100 (see also Madsen et al 1983;Deffieux et al 2009;Chen et al 2013).…”
Section: New Methodsmentioning
confidence: 82%